Ethanol exacerbates manganese - induced functional alterations along the hypothalamic-pituitary-gonadal axis of male rats (2018)
Manganese (Mn) exposure has been reported to induce reproductive dysfunction in animal and humans. Studies have shown that a large percentage of adolescent and adult populations tend to consume alcohol in a binge pattern. However, there is no information on the influence of alcohol on Mn - induced functional alteration along the hypothalamic - pituitary - gonadal axis. This study aimed to evaluate the influence of ethanol (EtOH) on Mn - induced functional alteration along the hypothalamic - pituitary - gonadal axis. Rats were exposed to Mn alone at 30 mg/kg body weight or co-expose with EtOH at 1.25 and 5 g/kg body weight for 35 consecutive days. Results showed that EtOH exposure significantly (p < 0.05) exacerbated Mn - induced decrease in anti- oxidant enzymes activities, glutathione level and increased oxidative stress biomarkers in the hypothalamus, testes an epididymis of the exposed rats. Moreover, induction of inflammation was associated with disruption of histo-architecture of the hypothalamus, testes and epididymis of rats treated with Mn alone, EtOH alone or in combination. Furthermore, EtOH significantly exacerbated Mn - induced diminution in reproductive hormones and marker enzymes of testicular functions coupled with decreased sperm quantity and quality. Taken together, EtOH exacerbates Mn - induced functional alteration along the hypothalamic - pituitary - gonadal axis in rats via mechanisms involving induction of oxidative/nitrosative stress, lipid peroxidation and inflammation in rats.